Addendum: Immobilization of trypsin in lignocellulosic waste material to produce peptides with bioactive potential from whey protein. [Materials, 9, 5, (2016), (357)] - Bassan, Juliana Cristina [UNESP]; Bezerra, Thaís Milena de Souza [UNESP]; Peixoto, Guilherme [UNESP]; Da Cruz, Clariana Zanutto Paulino [UNESP]; Galán, Julián Paul Martínez [UNESP]; Vaz, Aline Buda dos Santos [UNESP]; Garrido, Saulo Santesso [UNESP]; Filice, Marco; Monti, Rubens [UNESP] (MDPI, 2016)
The authors would like to add the following sentence to the Acknowledgments section of their article [1]: The authors thank Programa de Apoio ao Desenvolvimento Científico da Faculdade de Ciências Farmacêuticas da UNESP-PADC for their financial support.